AI-Integrated Public Digital Infrastructure for Geopark Tourism: Empowering MSMEs through Smart Mobility and Data-Driven Governance - Helmi Bahar Alim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study develops an integrated digital platform architecture as a systemic response to two structural challenges in the Kebumen Geopark: the economic exclusion of Micro, Small, and Medium Enterprises (MSMEs) from the digital tourism value chain, and the fragmentation of mobility services that reduce operational efficiency and visitor experience. Using a conceptual design methodology grounded in Critical Interpretive Synthesis (CIS), Comparative Policy Analysis (CPA), and contextual needs mapping, the study identifies three critical interdependencies between MSME empowerment, smart mobility, and parking management. These interdependencies form the basis of a validated integration architecture that, based on simulation and expert review, reduces average visitor wait times by 18% and increases MSME digital participation by 27%. The platform integrates modular components for MSME visibility, mobility optimization, and participatory governance through data-driven decision support. Validity was established through expert interviews (N=15) involving digital tourism practitioners, policymakers, and system designers, complemented by comparative analysis with five leading global smart tourism models (Jeju, Smart Santander, Magelang, Banyuwangi, and Yogyakarta). Theoretically, this research advances the Smart Tourism Ecosystem framework by embedding civic-oriented governance and data sovereignty into the system design. Practically, it delivers a replicable Public Digital Infrastructure (PDI) blueprint for inclusive and sustainable tourism governance in geoparks and similar non-urban destinations.